2021
DOI: 10.1002/tox.23399
|View full text |Cite|
|
Sign up to set email alerts
|

The biomechanistic aspects of renal cortical injury induced by diesel exhaust particles in rats and the renoprotective contribution of quercetin pretreatment: Histological and biochemical study

Abstract: Although several studies have reported a toxic effect of diesel exhaust particles (DEP) exposure on the kidney tissues, the involvement of autophagy/NF-kB signaling as encountered mechanisms and the protective effects of a natural flavonoid, quercetin on DEP remains unclear. Thirty-two albino rats were divided as control, quercetintreated (60 mg/kg, oral), DEP-exposed (0.5 mg/kg, intra-tracheal), and quercetin/DEPexposed groups. Specimens of the renal cortex were subjected to histo-biochemical study and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Specifically, with the development of industrial technology and the progress of science and technology, the damage of chemical raw materials to the kidney has grown immensely prominent. Data from animal models have shown that the protective effect of quercetin is closely related to the clearance of free radicals and reduction of lipid peroxidation in both industrial chemical raw materials and heavy metal and diesel particulate pollution (Li et al, 2016b;Qi et al, 2017;Uthra et al, 2017;Alshanwani et al, 2020;Morsi et al, 2022). Moreover, Quercetin was also found to reduce organophosphorus pesticide mixture-induced nephrotoxicity by regulating fatty acid, energy and sex hormone metabolism, protecting antioxidant defense systems and reducing DNA damage (Qi et al, 2017).…”
Section: Quercetin In Traditional Herbal Medicinesmentioning
confidence: 99%
“…Specifically, with the development of industrial technology and the progress of science and technology, the damage of chemical raw materials to the kidney has grown immensely prominent. Data from animal models have shown that the protective effect of quercetin is closely related to the clearance of free radicals and reduction of lipid peroxidation in both industrial chemical raw materials and heavy metal and diesel particulate pollution (Li et al, 2016b;Qi et al, 2017;Uthra et al, 2017;Alshanwani et al, 2020;Morsi et al, 2022). Moreover, Quercetin was also found to reduce organophosphorus pesticide mixture-induced nephrotoxicity by regulating fatty acid, energy and sex hormone metabolism, protecting antioxidant defense systems and reducing DNA damage (Qi et al, 2017).…”
Section: Quercetin In Traditional Herbal Medicinesmentioning
confidence: 99%
“…Dates from animal models of AKI have shown that quercetin increases antioxidant (GSH, vitamin C, vitamin E, etc.) levels (Kahraman et al, 2003;Renugadevi and Prabu, 2010;Kinaci et al, 2012;Nabavi et al, 2012;Sanchez-Gonzalez et al, 2017), strengthens the enzymes activity of GSH, CAT, SOD (Inal et al, 2002;Kahraman et al, 2003;Singh et al, 2004;Renugadevi and Prabu, 2010;Yao et al, 2011;Nabavi et al, 2012;Erboga et al, 2015; Frontiers in Pharmacology frontiersin.org Elbe et al, 2016;Sanchez-Gonzalez et al, 2017;Yuksel et al, 2017;Gholampour and Sadidi, 2018), decreases the concentration of oxidants (e.g., MDA) (Kinaci et al, 2012;Erboga et al, 2015;Elbe et al, 2016;Yuksel et al, 2017;Gholampour and Sadidi, 2018), and reduces renal lipid peroxidation (Singh et al, 2004;Renugadevi and Prabu, 2010;Chaudhary et al, 2015;Gholampour and Sadidi, 2018;Morsi et al, 2022).…”
Section: Antioxidantsmentioning
confidence: 99%
“…Therefore, the distribution and toxicity of PM mainly depend on particle size [ 8 ]. Exposure to PM has been reported to adversely affect the respiratory [ 9 ], cardiovascular [ 10 ], renal [ 11 , 12 ], hepatic [ 13 ], dermal [ 14 ], and nervous systems [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Short-term (24 h exposure to PM significantly narrowed retinal vessels, as well as both arterioles and venules in healthy adults [ 30 ]. Toxicological studies suggest that acute respiratory PM exposure causes retinal edema, which may be mediated by hypoxic responses [ 12 ]. In another rodent-based study, PM exposure in the eye triggered retinal vascular permeability, with retinal edema and inflammation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%